Efeito da interação genótipo x ambiente na qualidade fisiológica de sementes de soja (Glycine max (L) Merrill) - Krenski, Antonio (2005)
Soybean production depends on the technology applied associated with scientific know how and availabilities destined to the productive sector. Seed companies associated with plant breeding companies have contributed a lot of with the soybean production in Brazil. The Brazilian production that will be harvest in 2005/2006 will have to reach 58,7 million tons before the previous one of 51,1 million tons, however the sown area have to fall 6,4 percent for 21,9 million hectares. According to IBGE the estimate of bigger production is based on the expectation of better climate conditions during soybean production in this year. To preserve the genetic and physiological maximum potential of one cultivar it is necessary to know its adaptation in environments where the seeds will be produced, to identify, to correlate the genotypes, to determine its productive capacity, in the physiological and sanitary level. The goal of this work was to evaluate the performance of five soybean genotypes from different maturity groups in six environments (contrasting latitudes and altitudes), with intention to determine variations in the seed quality. Among different environment tested Abelardo Luz was the best place to produce soybean seeds. São Miguel do Iguaçu and Maracaju were high restrictive to soybean seed production. Genotypes from different maturation groups have different seed quality performance in different environment.